Evolution of river planforms downstream of dams: Effect of dam construction or earlier human‐induced changes?. Issue 10 (1st April 2018) - Słowik, Marcin; Dezső, József; Marciniak, Adam; Tóth, Gabriella; Kovács, János
Abstract: When studying the evolution of landscape, it is difficult to discriminate the influence of anthropogenic from natural causes, or recognise changes caused by different sources of human action. This is especially challenging when the influence of certain sources is overprinted. For instance, although dam closure is the most common method of altering river courses, dam construction is often preceded by hydro‐technical works such as channel straightening, embankment construction or sediment mining. Both dam construction and the hydro‐technical works that precede dam closure can result in changes in the balance between sediment supply and transport capacity, and often, changes in river planform. The main objective of this study was to verify whether the works preceding dam closure are an important driver of river planform changes on the lower Drava River (Hungary). The case study is based on geological and geophysical surveys, as well as the analysis of historical maps covering an anabranching, 23 km long valley section. We show that channel straightening conducted prior to dam closure resulted in a transition from a meandering to sinuous planform with channel bars. Dam construction itself then caused enhanced incision, exposure of bar surfaces, vegetation encroachment and the formation of an anabranching planform. Based on this study, we developed models of alluvial island and channel planform evolution downstream of dams. Dam construction enhances channel incision, narrowing, and the reduction of flow caused by earlier hydro‐technical works. Many rivers downstream of dams experience episodes of anabranching or wandering, with a multi‐thread pattern replacing sinuous, braided and meandering courses. When incision continues, river patterns evolve from anabranching to sinuous via the attachment of alluvial islands to floodplains. However, the timing and sequence of these changes depend on hydrological and sediment supply regimes, geomorphic settings and anthropogenic actions accompanying dam construction. Copyright © 2018 John Wiley & Sons, Ltd. Abstract : The main objective of this study was to verify whether the works preceding dam closure are an important driver of river planform changes. Based on research conducted in the lower Drava Valley (Hungary), we developed models of alluvial island and channel planform evolution downstream of dams. Dam construction enhances channel incision, narrowing and reduction of flow caused by earlier hydro‐technical works. When incision continues, river patterns evolve from anabranching to sinuous via the attachment of alluvial islands to floodplains.